Multilingual Creative Reformists: Saudi Arabian Women's Ingenuity in Overcoming Economic, Religious and Cultural Barriers to Career Success - Riedy, Robbin T. Thornton (My University, 2013)
The King Abdullah Foreign Scholarship Programs gives thousands of young Saudi Arabian women the opportunity to study abroad, learn English, and earn advanced degrees. How do students from this religiously conservative nation, studying at two Washington universities, construct career aspirations within a rigid structure in which they face economic, religious and cultural constraints? Women employed many passive resistance strategies to overcome these barriers. Students interviewed all chose to work within the system rather than defy it. The gender attitude of women also impacted how they dealt with various limitations. Those with more egalitarian views pushed the boundaries slightly more than those with more essentialized gender perspectives.
Thesis (Master's)--University of Washington, 2013
Keywords: English as a second language; Gender; King Abdulla Foreign Scholarship Program; Saudi Arabia; Second Language Acquisition; Study Abroad; Education; English as a second language; education - seattle